FESTIVAL GIZI SEHAT DAN SEIMBANG SEBAGAI STRATEGI PROMOSI GIZI DI DESA KENCANA MULIA, KECAMATAN RAMBANG, KABUPATEN MUARENIM - Muhammad Ridwan afandi; Mellza Anggreini; Ahmad faruq; Hesti Indian Wikia Putri; Rahma Haifa Nada; Nefi Vutia Sari; Reva Pradita Wulandari; Zahrah Khairunnisa; Afifah Putri Aulia; Indri Eka Putri; Nazhiifah Shandrina Adani; Shanti Oktaviandi; Chalisa Salsabila Faizal (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2025)
Food security plays a strategic role in supporting the creation of a healthy and independent society. This issue is a major concern, both globally and nationally. Internationally, this is summarized in the second Sustainable Development Goal (SDG), Zero Hunger, which focuses on ending hunger through achieving food security, improving nutrition, and sustainable agriculture. Additionally, this initiative contributes to SDG 3: Good Health and Well-being. Furthermore, it is also relevant to SDG 1: No Poverty. In Kencana Mulia Village, Rambang Sub-district, Muaraenim District, the community's dietary patterns remain monotonous and lack variety, potentially leading to nutritional deficiencies. In response to this situation, students from the Field Learning Experience (PBL) program at the Faculty of Public Health, University of Sriwijaya, initiated the Healthy and Balanced Nutrition Festival. This program is designed to enhance residents' knowledge and awareness of the importance of consuming diverse, nutritious, balanced, and safe food, using a participatory-educational approach. The series of activities included educational sessions on balanced nutrition and reducing food waste, a menu creation competition titled “My Plate” for mothers, and a coloring competition titled “My Plate” for children. The program received a positive response from the community, as evidenced by the high level of enthusiasm and increased understanding among participants. Additionally, the activities educated the community on utilizing local food ingredients and strengthened the role of mothers in making nutritional decisions within the family. The active participation of health workers and support from village officials further contributed to the program's success. The results of the implementation indicate that this festival is an effective tool for promoting nutrition at the village level and is worthy of being implemented sustainably in other areas with similar characteristics.